Rancang Bangun Mesin Hot Press Hidrolik 10 Ton Untuk Cetakan Spesimen Bahan Uji Komposit Fiberglass - jenal, Jenal Sodikin; Ariawan, Radhi; Ardiansyah Pradana, Rizky Nur; Dwi Cahyo, Rizal Agung (P3M Politeknik Negeri Cilacap, 2025)
Hydraulic Press Machines are also called composite molding machines, 10 ton hot hydraulic press machines are used to print fiberglass composite test material specimens, made to press FRP material into a certain shape so that it is easy to carry out further testing. In order to print test specimens for fiberglass composite test materials, the research aims to design, carry out calculations, and carry out function test of the machine. A hydraulic pressure of 10 tons was chosen to test the specimen whether at the specified maximum pressure the material could survive after further testing. The VDI 2222 engineering approach is used in machine design. Solidworks 2020 is used to get the design shape. With a compression force capacity of 10 tons, the pressure system design produces dimensions of 600 x 100 x 700 mm. consists of several parts such as a pressure gauge with a capacity of 20 tons, a set of temperature sensors, a timer, a sliding shaft, a 20 mm linear bearing, a 24 volt DC wiper motor, a 10 ton hydraulic jack, and a crank system as a transmission. Based on the test results, the pressure gauge can read the pressure produced by the jack, the temperature sensor can read the heat used, namely 110ËšC, and the wiper motor can operate up to a maximum pressure of 3 tons. The pressure system can function effectively if a manual pressure of 10 tons is applied. Tests show that using a temperature of 100ËšC for 10 minutes gives the best results.